Marketing Communication Strategy through Instagram social media @meraciklatte to increase consumer purchasing interest - Fatur Rahman Subhan; Erwan Sudiwijaya (Jogjakarta Communication Conference (JCC), 2026)
This study aims to analyze the marketing communication strategy through the Instagram social media account @meraciklatte in increasing consumer purchasing interest in coffee and matcha sachet products. This study uses a descriptive qualitative method with a phenomenological approach. Data were obtained through in-depth interviews with owners, social media admins, and consumers, and supported by Instagram content documentation. The analysis was conducted based on the stages of content marketing in the Marketing 4.0 concept and the AISAS (Attention, Interest, Search, Action, Share) model. The results show that the marketing communication strategy of @meraciklatte is carried out through setting clear goals, mapping the target market of the younger generation and urban consumers, planning and creating aesthetic and informative visual content, consistent distribution, reinforcement through interaction and collaboration, and evaluation based on Instagram insights. These strategies are able to build attention, interest, information searches, and encourage purchasing actions and sharing activities by consumers. Thus, Instagram plays an effective role as a marketing communication medium in increasing consumer purchasing interest at Meraciklatte.